Home Literacy Environment of African American Head Start Children - Janese Daniels (Intelektual Pustaka Media Utama, 2012)
Researchers have documented culturally specific family literacy practices in which low-income families engage, which are often a function of the context in which the family is currently embedded. These practices are well documented in ethnographic literature. Although this evidence exists, its utility is limited due to small sample sizes and lack of quantitative documentation on their contribution to children’s language and literacy development. This study attempted to quantify those culturally specific family literacy practices. 51 low-income African-American mother-child dyads participated. The contribution of multiple literacy practices was examined in relation to child language and literacy outcomes. Most low-income African-American families engaged in multiple literacy practices. Recommended areas for future research directions are discussed.